All services, all the time : how business services serve your business - McDavid, Doug. (Service systems and innovations in business and society collection., 2016)
This book takes the position that organizations, such as businesses and government agencies, form a special class of living system. As such they come into being, live through lifecycle stages, and can experience organizational health and various forms of organizational illness along the way. If the latter is frequent or extended, such organizations often die an untimely death. A services perspective can go a long way to combat this outcome and assist in maintaining organizational health. Allowing this perspective to permeate an organization induces a consideration of its genuine value and leads to a greater understanding of the breadth of stakeholders who are the beneficiaries of it. Productivity and services in an organization are symbiotic and must be so in order to achieve the balance that is key to the health of each organization. A services perspective illuminates as well the pivotal role that business-to-business service providers play in ensuring that balance is achieved and maintained. This book explores these factors from the point of view of the business leader and anyone concerned with the health of any organization.